Analisis Pengaruh Obat Antituberkulosis Terhadap Nilai Sgpt dan Sgot pada Pasien Penderita Tuberkulosis Paru - Nur Hasanah; Dede Rival Novian (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
Tuberculosis (TB) is a direct infectious disease caused by Mycobacterium tuberculosis. Anti-tuberculosis drugs have a hepatotoxic effect that causes extensive liver injury and harvesters. The parameter to determine the presence or absence of liver damage is to look at SGPT and SGOT levels. The purpose of this study was to determine the effect of drugs on SGPT and SGOT values based on age and sex classification. The method is carried out with a retrospective approach. The results showed that the effect of drugs on the value of SGPT with a high value of 35 as much as 6.25%, on the value of SGOT with a high value 35 as much as 12.5%. Whereas at the age of 56-65 years the SGPT value was 2.5% and SGOT was 3.75%, at the age of 17-25 years the SGOT value was 3.75%. sex with a high SGPT score of 5%. While the SGOT value is equal to 6.25%. Then it can be concluded that the administration of anti-tuberculosis drugs to the value of SGPT and SGOT has an effect on the value of SGPT and SGOT based on age is productive age which is 15-49 years whereas based on gender is men.